Network Capability Exposure Scheme in Satellite and Ground Merged Network - Lin LIN; Bin ZHU; Zelin WANG; Guangquan WANG; Jianwei HE; Haipeng YAO (天地一体化信息网络)
Facing the issue of the integration capability opening of terrestrial 5G network and satellite communication network fusion architecture, first the research status of 5G and satellite communication fusion at home and abroad was introduced.Then a layered architecture for consistent capability opening under the fusion architecture of satellite and terrestrial 5G networks was proposed.Finally, the open requirements, feasible architecture and application scheme of consistent capability under the fusion architecture of satellite and terrestrial 5G networks was discussed.Through the proposed capability opening scheme based on the integration of 5G and satellite communication network, on the one hand, the capability invocation path of satellite communication network and terrestrial 5G network was connected, and 5G capability was extended to the application in the fi eld of satellite communication.On the other hand, the platform provided technical reference for satellite management system information for 5G capability decision-making and 5G network capability for satellite link selection.